Pengaruh Umur Pemotongan Terhadap Produksi dan Kualitas Nutrisi Tanaman Indigofera (Indigofera Sp) - Erlis Setiyaningrum; I Nyoman Kaca; Ni Ketut Etty Suwitari (GEMA AGRO, 2018)
This study was held at BPTU-HPT Denpasar which located in Pangyangan Village, Pekutatan Sub-district, Jembrana Regency conducted from January 18, 2017 - April 18, 2017. Analysis of nutritional content was performed at the Laboratory of the Agriculture Faculty of Warmadewa University and the Udayana University Faculty of Animal Husbandry Laboratory. The purpose of this study to determine the effect of cutting age on production and quality of nutrition Indigofera sp.The Method of this study did use on Complete Randomized Design (CRD) which consisted of 3 groups and 4 treatment of cutting age. The treatments in this study were P1 (45 days of Cutting Age), P2 (60 days of cutting age), P3 (75 days of cutting age), and P4 (90 days of cutting age). The results showed that the effect of different cutting age gave a most real effect (P